Association between remnant cholesterol and low-density lipoprotein cholesterol discordance and type 2 diabetes or prediabetes: results from NHANES - Yijing Xin; Yimeng Wang; Yuyuan Shu; Hanyang Liang; Yanmin Yang (BMC Endocrine Disorders)
Abstract Objective There is limited evidence on the relationship between remnant cholesterol (RC) and low-density lipoprotein cholesterol (LDL-C) discordance and type 2 diabetes or prediabetes. This study aimed to investigate the association between RC and LDL-C discordance and type 2 diabetes or prediabetes in the general US adult population. Methods Data from 19,604 participants in the National Health and Nutrition Examination Surveys (NHANES) (2005–2018) were analyzed. The percentile difference between RC and LDL-C was used to define discordance. Logistic regression models were performed to assess the relationships between RC, LDL-C, RC and LDL-C percentile difference, LDL-C and RC discordant. Nonlinear relationships were explored using restricted cubic splines. Mediation analysis was conducted to evaluate the direct and indirect relationships between abdominal obesity and type 2 diabetes through RC. Results RC was non-linearly and J-shaped correlated with type 2 diabetes and prediabetes, whereas LDL-C was non-linearly and U-shaped correlated with type 2 diabetes and was S-shaped correlated with prediabetes. Compared to concordant participants, those with discordantly low RC population had lower type 2 diabetes odds, while those with the discordantly high RC population had higher type 2 diabetes and prediabetes odds. When a clinical LDL-C cut-off of 2.60 mmol/L was applied, participants in the high LDL-C and low RC group had the lowest odds of type 2 diabetes, while those in the low LDL-C and high RC group had the highest odds. Significant interactions between LDL-C and RC discordance and factors such as age, MetS, and lipid-lowering medications were observed in relation to type 2 diabetes odds. RC was found to mediate 15.86% of the association between abdominal obesity and type 2 diabetes, and 16.22% of the association between abdominal obesity and prediabetes in the non-diabetes population. Conclusions Discordantly high RC was associated with higher odds of type 2 diabetes and prediabetes, while discordantly low RC was associated with lower odds of type 2 diabetes.